Effects of 2-amino-4,6-di-tert-butylphenol derivatives on the viability and functional state of human peripheral blood lymphocytes - Nizheharodava, Darya B.; Ksendzova, Galina A.; Sysa, Aliaksei G.; Yurkevich, Mariya Yu.; Labai, Maryna V.; Shadyro, Оleg I.; Zafranskaya, Marina M. (Experimental Biology and Biotechnology, 2020)
Derivatives of 2-amino-4,6-di-tert-butylphenol exhibit antiviral properties and radical regulatory activity against various types of organic radicals which determines the actuality of their further investigation. But the question of aminophenol derivatives immunomodulatory activity remains open. In this regard, the aim of the study was to assess the effects of 2-amino-4,6-di-tert-butylphenol derivatives on the viability and functional potential of human peripheral blood lymphocytes. As a result of the studies, it was shown that aminophenol compounds at concentrations of 10–5–10–7 mol did not exert a toxic effect while at a concentration of 10–4 mol showed a cytotoxic effect due to the induction of secondary necrosis. Compounds N-(2-hydroxy-3,5-di-tert-butylphenyl)-4-methylbenzenesulfonamide and 2,4-di-tert-butyl-6-morpholinophenol at a concentration of 10–6 mol stimulated the extracellular production of α-interferon by peripheral blood mononuclear cells and intracellular production of γ-interferon by CD3+T-lymphocytes. An immunosuppressive effect (more than 50 %) of N-(2-hydroxy-3,5-di-tert-butylphenyl)-4-methylbenzenesulfonamide and 2,4-di-tert-butyl-6-morpholinophenol compounds at a concentration of 10–5 mol was revealed to the mitogen-induced proliferation of T-lymphocytes.
Keywords: 2-amino-4,6-di-tert-butylphenol derivatives; immune system; lymphoid cells; interferons; proliferation; cytotoxicity